(untitled) (Web of Teachers: Inderscience Research, 2025)
This article examines the application of digital technologies in composition education to enhance students’ creative thinking, visual perception, and technical literacy. The importance of improving teachers’ professional competence and implementing innovative pedagogical methods is also highlighted.